The use of tamoxifen in the treatment and prevention of breast cancer - Hołowczuk, Magdalena; Janeczko, Dominika; Orzeł, Anna; Klatka, Barbara; Terpiłowski, Michał; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2019)
Breast cancer is the most frequently occurring malignant neoplasm among women. Statistically, it constitutes 22,8% of all malignant neoplasms among females. Despite the fact that the causes of the disease remain unknown, a few risk factors are contributing to its development. Age, family history, type of lifestyle, hormones and genetic background have a significant association with occurrence of breast cancer. Due to the fact that time in which female sex hormones affect mammary gland is one of the most important risk factors of breast cancer development, more researchers focused on the use of drugs such as selective estrogen receptor modulators (SERMs) in the disease prevention. Tamoxifen has antiestrogenic effect. That results in the inhibition of both- growth factors release and synthesis by the tumour. Moreover, this drug works as agonist, replacing oestrogen to many tissues, such as the ones in liver, bone, breast and uterus. In the literature there are many reports about the effectiveness of tamoxifen in the prevention of breast cancer. The drug, in addition to using it as adjuvant therapy for breast cancer, can be used as a prophylactic of the disease. Side effects of the drug are rare, but they can not be completely excluded. Breast cancer, which is currently the most common tumour in the globe, is a serious worldwide public health quandary. Tamoxifen is considered to be a pioneering drug as it is used in combined breast cancer therapy and also in chemoprophylaxis ,but every case of using the medicine should be considered individually to assess benefit-risk ratio.